Evaluation of ground glass nodules. Issue 4 (July 2018) - Mironova, Varvara; Blasberg, Justin D.
Abstract : Purpose of review: Ground glass nodules (GGNs) represent an indolent subset of lung nodules including preinvasive nonsmall-cell lung cancer associated with a favorable prognosis and low risk for progression. Increased performance of screening cat-scan (CT) for high-risk patients has identified an increasing number of GGNs. The management of these nodules is founded mostly on single institution data and currently no universally accepted recommendations help guide clinicians managing these patients. Recent findings: The solid component within a GGN is the key determinant of prognosis and is best defined by evaluating nodule density on mediastinal windows of a chest CT. When a GGN is small (<3 cm), associated with minimal change in size (<25% growth per year), and there is no demonstration of a significant solid component on mediastinal windows (<2 mm in diameter), patients can be safely observed with serially imaging. These imaging features also help distinguish patients that may harbor early-stage lung cancers that benefit from local treatment options. Summary: The majority of GGNs do not undergo significant progression during surveillance. Evidence of nodule progression on interval imaging may be a trigger for consideration of a local treatment option such as surgical resection. Large prospective studies are needed in the United States to validate the more robust data derived from Asian studies to help formulate formal recommendations for surveillance and treatment. Future improvements in imaging and the molecular characterization of these GGNs may further refine which patients are at risk for progression.